DESIGNING POVENTURE AS SUPPLEMENTARY TEACHING MATERIAL FOR TEACHING READING ON DESCRIPTIVE TEXT - Khotimah, Husnul; Salam, Urai; Rosnija, Eni (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis research was conducted to design a teaching material needed by the teacher and students in reading on descriptive text to supportCTLApproach. The material is called Poventure which is the abbreviation of Pontianak Adventure. The research was conducted atSMPNegeri 11 Pontianak with the eighth grade students in academic year 2016/2017 and their English teacher as the participants. The research applied R&D with three phases of development called ADDIE. From the need analysis, it was found that the students need interesting supplementary material to improve their reading comprehension on descriptive text. The research focused on creating the material to fit in the needs. In the research, the design of Poventure covered the concept of the product, while the development of Poventure described the contents and approach included in the product. To validate the product, an expert validation is used with the result of 3.75. This result meant that Poventure is a very good supplementary teaching material for teaching reading on descriptive text to support Contextual Teaching and Learning for grade eighth students at SMPN 11 Pontianak in academic year 2016/2017.Â Keywords: Poventure, Descriptive Text, Reading, CTl, Development Research